A study on the perceptions of the Institute of Library and Information Science students on library and information science electives - Wong, Jose Raphael M (School of Library and Information Studies, University of the Philippines Diliman, 2007)
The field of Library and Information Science is often subjected to developments. In order to adapt to these changes, the UP Institute of Library and Information Science (ILIS) offers electives in information systems, health/medical librarianship, law librarianship, archives and records management and general librarianship for the Bachelor of Library and Information Science (BLIS) program.